Post-operative benefits of Tisseel(®)/Tissucol(®) for mesh fixation in patients undergoing Lichtenstein inguinal hernia repair: secondary results from the TIMELI trial - Campanelli, G. (Springer Paris, 2014)
PURPOSE: The Tisseel/Tissucol for mesh fixation in Lichtenstein hernia repair (TIMELI) study showed that mesh fixation with human fibrin sealant during inguinal hernia repair significantly reduced moderate–severe complications of pain 12 months post-operatively compared with sutures. Further analyses may assist surgeons by investigating predictors of post-surgical complications and identifying patients that may benefit from Tisseel/Tissucol intervention. METHODS: Univariate and multivariate analyses identified risk factors for combined pain, numbness and groin discomfort (PND) visual analogue scale (VAS) score 12 months post-operatively. Variables tested were: fixation method, age, employment status, physical activity, nerve handling, PND VAS score at pre-operative visit and 1 week post-operatively. The effect of fixation technique on separate PND outcomes 12 months post-surgery was also assessed. Analyses included the intention-to-treat (ITT) population and a subpopulation with pre-operative PND VAS > 30 mm. RESULTS: 316 patients were included in the ITT, with 130 patients in the subpopulation with pre-operative PND VAS > 30. Multivariate analysis identified mesh fixation with sutures, worsening pre-operative PND and worsening PND 1 week post-surgery as significant predictors of 12-month PND in the ITT population; mesh fixation with sutures was a significant predictor of 12-month PND in the pre-operative PND VAS > 30 subpopulation (p < 0.05). Mesh fixation with Tisseel/Tissucol resulted in significantly less numbness and a lower intensity of groin discomfort compared with sutures at 12 months; there was no difference in pain between the treatment groups. CONCLUSIONS: Pre-operative discomfort may be an important predictor of post-operative pain, numbness and discomfort. Tisseel/Tissucol may improve long-term morbidity over conventional sutures in these patients.